PENGGUNAAN KONSEP TALFÄªQ SEBAGAI SALAH SATU KAEDAH PENYELESAIAN HUKUM SYARAK: SATU ULASAN LITERATUR - Jamaludin, Mohd Hafiz; Buang, Ahmad Hidayat (Journal of Shariah Law Research, 2017)
The scenario of the ummah currently is moving rapidly, causing the scholars to act fast in providing the best solutions for every problem arise. The concept of talfīq is a method frequently used by scholars nowadays although it is not categorized as one of the sources of Islamic law. Talfīq can be defined as mixing or combining various opinions of scholars in a specific problem without being bound to any of the madhhabs (schools of law). This concept still needs clarification from the experts of Islamic law, particularly the discussions on the arguments among the scholars. The scholars in the past strongly opposed the usage of this concept. However, the current development of Islamic jurisprudence has popularized the use of talfīq, making reference to all madhhab possible. This study found that the concept of talfīq requires further explanation as far as discussions on its authority, so that an accurate assessment can be made on whether to support the implementation of the talfīq or totally disapproved its use. Positive and negative impact from the use of talfīq will also need to be emphasized in order to act as a guidance for scholars when using this concept in the process of providing legal solution in Islamic law